2004
DOI: 10.1007/s00520-003-0507-z
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of refractory chemotherapy-induced diarrhea (CID) with octreotide long-acting formulation in cancer patients: 11 case studies

Abstract: The ability of octreotide LAR 30 mg to speed the resolution of CID and limit further episodes of diarrhea to infrequent NCI grade 1 controlled with loperamide (prn) suggests that long-acting somatostatin homologues have the potential to be useful in the secondary prevention of diarrhea in patients undergoing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Approximately 65% of patients with CID require a lower dose (i.e., fewer mg/kg) at some point in their chemotherapy courses, 45% require fewer doses (i.e., less often), and 71% experience a temporary or permanent cessation of treatment (96). Pharmacologic treatments for CID include loperamide as well as some off-label use of octreotide and tincture of opium, all of which offer limited benefit in mild diarrhea and minimal benefit in severe CID (101, 110114). More complicated cases require vigilant medical monitoring, aggressive pharmacologic treatment, intravenous fluids in outpatient settings, and even hospitalization (101).…”
Section: Alleviating Irinotecan-induced Enteropathymentioning
confidence: 99%
“…Approximately 65% of patients with CID require a lower dose (i.e., fewer mg/kg) at some point in their chemotherapy courses, 45% require fewer doses (i.e., less often), and 71% experience a temporary or permanent cessation of treatment (96). Pharmacologic treatments for CID include loperamide as well as some off-label use of octreotide and tincture of opium, all of which offer limited benefit in mild diarrhea and minimal benefit in severe CID (101, 110114). More complicated cases require vigilant medical monitoring, aggressive pharmacologic treatment, intravenous fluids in outpatient settings, and even hospitalization (101).…”
Section: Alleviating Irinotecan-induced Enteropathymentioning
confidence: 99%
“…For patients with refractory CID, octreotide LAR may shorten the duration of diarrhoea, thus improving the quality of life by decreasing abdominal cramping and diarrhoea. 22 Based on results from clinical studies, octreotide LAR may be administered as a prophylactic agent prior to chemotherapy or the next cycle of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In several patients who developed refractory CID towards conventional therapy, octreotide LAR sped up the resolution of CID and limited further episodes of diarrhoea during subsequent cycles of chemotherapy. 22 Another study indicated that octreotide LAR can be used as a secondary preventive approach in patients experiencing grade 2–4 CID, and monthly injections reduced the incidence of diarrhoea while the chemotherapeutic regimen was completed. 23 However, inconsistent results were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…This formulation has demonstrated efficacy in resolving severe diarrhea and preventing further episodes of diarrhea in patients receiving ongoing therapy. 70 Other Agents. Budesonide is an orally administered, topically active steroid with high activity in IBD, a 90% first pass effect in the liver and, therefore, low systemic availability.…”
Section: Antidiarrheal Medicationsmentioning
confidence: 99%